Magnetic properties of van der Waals ferromagnet VI3 and CrI3: a renormalization group approach - Kaya, T. (INDIAN ASSOC CULTIVATION SCIENCE, 2024)
Motivated by the experimental findings and the available recent theoretical works of two-dimensional van der Waals ferromagnets, we calculated the critical coupling strength of VI(3 )and CrI(3 )monolayers. We expressed the monolayer Hamiltonian as pairwise interactions with the Using model and analyzed the problem with the renormalization group theory. We used the decimation transformation method while applying the renormalization group theory. Using the methods we developed earlier, we overcame the problem of the decimated lattice not being self-dual. Since the CrI(3 )and VI3 lattice structures are the same, the coupling constants K-m;c corresponding to these monolayers were calculated as 0.383; here index m denotes either CrI(3 )or VI3. Since the experimentally determined critical temperatures of these monolayers are also very close to each other, the exchange coupling energy J(m;c )corresponding to these monolayers was determined approximately as 3:2 chi 10(-22)Joule
Keywords: Van der Waals ferromagnetism; Renormalization group method; Critical phenomena; DUAL ISING LATTICES; INTRINSIC FERROMAGNETISM; Physics